The Religious Life in the Spain of Philip II and Philip III - Wright, Anthony D. 1947- (1985)
From the vividly autobiographic Life of St Teresa famous images of conventual life in sixteenth-century Spain have been derived; both the dark impression of unreformed monastic existence and the heroic profile of reformed regulars. Before and after that era the social, not to say political prominence of certain figures, friars and nuns, in Spanish life is notorious, from the reigns of the Catholic Monarchs to that of Philip IV and beyond. Modern historical research has indeed highlighted the contribution to political and ecclesiastical development, to early Catholic reform above all, of key members of the regular clergy under the Catholic Monarchs. For monastics, as opposed to mendicants, in post-medieval Spain, the extensive and meticulous researches of Linage Conde have put all Iberian scholars in his debt. The fascinating origins of the essentially Iberian phenomenon of the Jeronymites have recently received new attention from J.R.L. Highfield, but further insights into the true condition of the religious life in the Iberian peninsula of the supposedly Golden Age are perhaps still possible, when unpublished material is consulted in the Roman archives and in those of Spain, such as Madrid, Simancas, Barcelona and Valencia. Considerations of space necessarily limit what can be suggested here, but the development of monastic life in Counter-Reformation Spain is arguably best considered in its extended not just in its stricter sense: for parallels and contrasts, as well as direct influences, were not confined by the normal distinctions between the eremitic and the monastic, the monastic and the mendicant, the old and the new orders, or even the male and female communities. Furthermore the intervention of Spanish royal authority in Portuguese affairs between 1580 and 1640, not least in ecclesiastical and regular life, provides a useful comparative basis for consideration of truly Iberian conditions.